Observation on Binturong (Arctictis binturong) behaviour and its conservation management practices at Semarang Zoo, Central Java - Arini Diah Irawati Dwi; Fitriari Utami; Firdaus Muhamad Fahmi (BIO Web of Conferences, 2024)
The purpose of the study was to observe behaviour daily and investigate its management practices at the Semarang Zoo. Scan sampling was used to monitor the behaviours of three solitary binturongs in 3.0 × 1.5 m enclosures which reflected their solitary nature. Diurnal observations revealed that binturongs spent over 50% of their time sleeping and resting, consistent with their nocturnal habits. A daily diet of papaya, banana, cucumber, and chicken meat was provided to support their lives. Management strategies such as daily enclosure cleaning, freshwater supply, and health care every three months were implemented. It suggested that welfare could be enhanced by adding enrichment activities and increasing the variety of diets. Observations during daylight hours highlighted the need for further studies on both diurnal and nocturnal activity patterns. Conservation institutions believed that research on phylogenetics and genetic diversity of binturongs was critical for effective species conservation. Based on detailed observation and analysis, it was found that effective management practices significantly improved the welfare of captive binturongs. These findings provide essential insights into binturong behaviour and care, the development of best practices for zoo management as well as support for the ongoing conservation initiatives.